2008
DOI: 10.1111/j.1525-139x.2008.00441.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes after Failed Renal Transplantation—Does Dialysis Modality Matter?

Abstract: Patients returning to dialysis after graft loss (DAGL) are an increasing segment of the end-stage renal disease (ESRD) population. It is unclear whether patients with previous graft loss have equivalent or reduced survival from the time of restarting dialysis when compared with ESRD patients initiating dialysis for the first time. Moreover, the impact of dialysis modality on the survival of patients returning to DAGL is not known. Studies of patients with transplant graft failure returning to hemodialysis (HD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…kidney transplants (KT) fail each year and 20 % of patients on the kidney waiting list have had a previous failed KT [1][2][3]. Previous studies have reported that 25 to 50 % of surviving patients with kidney graft failure (GF) eventually undergo allograft nephrectomy (AN) [4][5][6][7][8][9].…”
mentioning
confidence: 99%
“…kidney transplants (KT) fail each year and 20 % of patients on the kidney waiting list have had a previous failed KT [1][2][3]. Previous studies have reported that 25 to 50 % of surviving patients with kidney graft failure (GF) eventually undergo allograft nephrectomy (AN) [4][5][6][7][8][9].…”
mentioning
confidence: 99%
“…Due to an absence of clear data on the subject, guidelines for which patients should undergo allograft nephrectomy, and at what time relative to resumption of dialysis, are lacking [35]. The potential benefits of allograft nephrectomy include removal of several harmful factors: a nidus of inflammation, the need for immunosuppression, and the presence of antigens that will raise the PRA over time and endanger future transplantation.…”
Section: In Summary – What Are the Risks And Benefits Of Allograft Nementioning
confidence: 99%
“…Again, studies have offered differing results when comparing survival outcomes of DAGL with transplant-naive patients on dialysis, depending on the specific cohorts studied and the duration of follow-up (6,7). In the majority of the studies, patients who commenced PD after graft loss experienced outcomes comparable to those with failed native kidneys (8,9). Differences in survival between PD and HD in DAGL patients has not been rigorously examined.…”
mentioning
confidence: 99%